Conscientious objection in euthanasia and assisted suicide: A systematic review. - Carlos Gomez-Virseda; Chris Gastmans (PLoS ONE, 2025)
Introduction As euthanasia and assisted suicide (EAS) become legal in more countries, conscientious objection (CO) of healthcare professionals is gaining increasing attention. While some argue that CO safeguards professionals' moral integrity, others view it as a barrier to patients' access to desired healthcare. This review provides a comprehensive synthesis of the ethical literature regarding CO to EAS and answers three key questions: What is the meaning of CO and how is it used in EAS? What ethical positions support or challenge it? What underlying presuppositions shape the debate?. Methods We used the PRISMA guidelines, RESERVE standards, and TARCiS statement to conduct a systematic review of argument-based publications retrieved from 13 major databases covering biomedical, philosophical, and theological literature. No date or language restrictions were applied. Titles and abstracts were independently screened by the two authors, and complete articles were selected based on predefined inclusion and exclusion criteria. Results We identified 58 pertinent articles that were included in our review. Of these, 51 were published in the last decade, from 2015 through 2024. Our findings highlight three key dimensions. First, while there is general agreement on the definition of CO, its interpretation and application in EAS remain highly contested. Second, the ethical debate revolves around three main positions: conscience absolutism, the compromise approach, and the incompatibility thesis. Each of these is supported by distinct ethical arguments. Third, the debate is shaped by several underlying presuppositions, including divergent views on conscience, morality, religion, medicine, and end-of-life care. Conclusions Our results highlight the risk of polarization in the debate on CO in EAS. It emphasizes the importance of dialogue between theoretical and context-sensitive perspectives to support more effective implementation of CO. Clearer guidelines are needed to balance respect for conscience, patient rights, and professional responsibilities in this complex issue.